PERANCANGAN PERANGKAT LUNAK BANTU PEMBELAJARAN MATA KULIAH PERANGKAT KERAS BERBASIS PHP - Cita St. Munthakhabah. R; Febriyani Syafri (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2021)
This research is a software development research that aims to develop learning aids software for hardware subjects based on PHP (Perl Hypertext Preprocessor) in the Computer and Informatics Engineering Study Program, Department of Electrical Engineering Education, Faculty of Engineering, Makassar University. The design of instructional media is carried out by collecting learning materials then designing the software and the necessary database. The learning media that has been created are then validated by two media experts. The objects in this study were 37 students of class 04 class 2012 Informatics and Computer Engineering Education Department of Electrical Engineering Education Faculty of Engineering, Makassar State University, as many as 37 people who program hardware courses in the even semester of the 2012-2013 academic year. Data collection was carried out using a questionnaire given to respondents. The results of the descriptive analysis show that the views of PTIK JPTE FT UNM students on the implementation of PHP learning media in the Hardware course are in the good category or equal to 91.89%.